Photocatalytic Inactivation of Escherichia Coli Aqueous Suspensions in a Fixed-Bed Reactor - Marugan, Javier (2014)
A fixed-bed, annular photoreactor is studied for the photocatalytic disinfection of Escherichia coli aqueous suspensions. Experiments were carried out under UV radiation employing P25 titanium dioxide immobilized onto glass Raschig rings. The photoreactor performance has been simulated following a predicted procedure that takes into account explicitly the radiation absorption step and a series-event disinfection mechanism. The modelling of the radiation field was carried out by Monte Carlo simulation. The reactor model has been compared with experimental data, being able to reproduce the evolution of the concentration of viable bacteria under different bacteria initial concentrations and irradiation levels.